2015
DOI: 10.1002/zoo.21235
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into resting behavior in Asian elephants in UK zoos

Abstract: Maintaining adequate welfare in captive elephants is challenging. Few studies have investigated overnight rest behavior in zoo elephants, yet time spent resting has been identified as a welfare indicator in some species. We investigated resting behavior in Asian elephants (Elephas maximus) in UK zoos, with the aim of identifying patterns or preferences in lying rest. Details of standing (SR) and lying (LR) rest behavior were identified by observing video footage of inside enclosures collected for 14 elephants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…However, the exact link between stereotypic behavior and welfare is still uncertain (Mason & Latham, ; Veasey, ), and additional measures of stress and welfare such as other behavioral indicators, health assessments, and fecal cortisol metabolite measures (Foley, Papageorge, & Wasser, ; Harris et al, ) are also important. Indeed, one recent study suggested even rest behavior itself may be used as a welfare indicator (Williams et al, ); therefore, no definitive conclusions will be drawn here.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the exact link between stereotypic behavior and welfare is still uncertain (Mason & Latham, ; Veasey, ), and additional measures of stress and welfare such as other behavioral indicators, health assessments, and fecal cortisol metabolite measures (Foley, Papageorge, & Wasser, ; Harris et al, ) are also important. Indeed, one recent study suggested even rest behavior itself may be used as a welfare indicator (Williams et al, ); therefore, no definitive conclusions will be drawn here.…”
Section: Discussionmentioning
confidence: 92%
“…One recent study found that captive Asian elephants lay down for just over 3 hr per day (Holdgate et al, 2016), slightly more than African elephants. Sleep patterns also vary considerably between captive populations (Williams, Bremner-Harrison, Harvey, Evison, & Yon, 2015). Management differences also affect behavior; one study found that a calf spent more time lying down at night when kept inside compared to outside (Posta et al, 2013).…”
Section: Captive Nocturnal Behaviormentioning
confidence: 99%
“…also Table 3). Literature data (Björk, 2011;Boyle et al, 2015;Braidwood, 2013;Friend, 1999;Friend & Parker, 1999;Gebbing, 1959;Gravett et al, 2017;Ibler & Pankow, 2012;Kandler, 2010;Kurt, 1960;Kurt et al, 2001;Laws et al, 2007;Meller et al, 2007;Posta, Huber, & Moore, 2013;Rönnborn, 2014;Tobler, 1992;Walsh, 2017;Weisz et al, 2000;Williams et al, 2015;Wuestenhagen et al, 2000) SCHIFFMANN ET AL.…”
Section: Observations On Correlation Between Lying and Standing Resunclassified
“…In mares late in gestation, reluctance to recumbent rest due to physical discomfort has been mentioned as well (Coomer & Fouché, ). In addition, previous research in captive elephants revealed reluctance of lying rest in situations where the animals do not feel completely safe (Laws et al, ; Roocroft, ; Williams, Bremner‐Harrison, Harvey, Evison, & Yon, ). Investigating effects of an inter‐zoo transfer of an adult Asian elephant bull, a significant change in resting behavior was reported (Laws et al, ).…”
mentioning
confidence: 98%
“…It is possible that this sleeping behaviour in proximity to the herd may represent times when one or more of the females was in oestrus, and the bull was demonstrating mate guarding behaviour, as seen in wild elephants (Poole, ). However, this may simply reflect a preference for proximity to other elephants when sleeping, as has been observed in cow/calf groups (Williams et al ., ).…”
Section: Challenges In Facilitating Natural Social Behaviour Of Bullsmentioning
confidence: 99%